Vozes amplificadas: o uso do LinkedIn na conscientização sobre misoginia estrutural, outdoor de mulheres demitidas após licença-maternidade - Amoedo, Raquel Almeida (Brasil, 2025)
This research aims to explore the role of LinkedIn as a tool to raise awareness about structural misogyny in the workplace and its effects on women's dismissal after maternity leave, considering that being a woman, mother and professional involves confronting structural misogyny in the corporate environment, inequality and gender violence, in addition to guaranteeing the rights of workers and expanding the academic and social debate. To this end, it is necessary to correlate, through published narratives, dismissals after maternity leave with structural misogyny in the corporate environment; analyzing, based on the narratives, the impact of these dismissals on the self-esteem and career prospects of these women; and investigating the influence and possible transformative role of LinkedIn in organizational cultures and practices. A qualitative, exploratory and descriptive research is then carried out, based on netnographic model, with observation and analysis of publications on the LinkedIn network. In view of this, it is verified that these publications have become a substantive and philosophical movement; due to the identification process, gaining repercussion and visibility generated from the exposure of these women-mothers-professionals affected by dismissal after returning from maternity leave, in search of listening, justice and support, as well as mobilization of professionals responsible for the organizational culture, promoting reflections and actions for internal changes.